Prediction of springback in multi-point forming. Issue 1 (1st January 2017) - Elghawail, Ali; Essa, Khamis; Abosaf, Mohamed; Tolipov, Abror; Su, Shizhong; Pham, Duc
Abstract: Flexible forming techniques, such as multi-point forming (MPF), are employed in manufacturing to reduce the time and cost of production. MPF uses a set of height-adjustable pins to construct free-form three-dimensional surfaces. Springback is a common phenomenon in forming including MPF which, if not properly catered for, will lead to parts that are out of specification. This paper introduces a detailed numerical approach for predicting springback in MPF. FE models were developed to simulate MPF of doubly curved panels in Aluminium alloy 5251-O. The Response Surface Method and the analysis of variance technique were employed to identify the most significant process parameters and to determine their optimal setting. The influence of these parameters on thickness variations across the formed panel and the subsequent effect of those variations on the amount of springback were investigated. It was found that the radius of curvature had the most significant effect on springback and thickness variation. Minimum springback can be achieved by introducing high strains through sheet stretching.